(untitled) (Global Journal of Management and Business Research, 2016)
Thomas Piketty’s (2014) Capital in the 21 st Century revolutionized economic thoughts on inequality. Started by the 2008/09 World Financial Crisis and cumulated in the subsequent Occupy movement, attention to rising inequality regarding economic wage, opportunity and wealth led to advocacy for a more equal society. Innovatively, this article argues for a mixture of equality and inequality within a societal network holding value when access to opportunities to transfer implicit wealth is distributed merit-based. By the example of Ivy League educational institutions, but also elaborating on social environments and interaction networks, a novel economic wealth transfer model is proposed. Within an economic system, dyads of unequal crystallized value based on heritage (e.g., royal families, legacy admits) and merit-based equality represented by offspring from families with underprivileged backgrounds, whose outperforming ambition, fluid intelligence and drive may lead to fruitful social interactions and beneficial wealth transfers, may create beneficial economic outcomes. On the societal level, within networks favorable environments may serve as transformation hubs if entered merit-based by underprivileged families.